A transit-amplifying population underpins the efficient regenerative capacity of the testis. - Carrieri, C; Comazzetto, S; Grover, A; Morgan, M; Buness, A; Nerlov, C; O'Carroll, D (Rockefeller University Press, 2017)
The spermatogonial stem cell (SSC) that supports spermatogenesis throughout adult life resides within the GFRα1-expressing A type undifferentiated spermatogonia. The decision to commit to spermatogenic differentiation coincides with the loss of GFRα1 and reciprocal gain of Ngn3 (Neurog3) expression. Through the analysis of the piRNA factor Miwi2 (Piwil4), we identify a novel population of Ngn3-expressing spermatogonia that are essential for efficient testicular regeneration after injury. Depletion of Miwi2-expressing cells results in a transient impact on testicular homeostasis, with this population behaving strictly as transit amplifying cells under homeostatic conditions. However, upon injury, Miwi2-expressing cells are essential for the efficient regenerative capacity of the testis, and also display facultative stem activity in transplantation assays. In summary, the mouse testis has adopted a regenerative strategy to expand stem cell activity by incorporating a transit-amplifying population to the effective stem cell pool, thus ensuring rapid and efficient tissue repair.